Differential sympathetic nerve and heart rate spectral effects of nonhypotensive lower body negative pressure - Floras, J S; Butler, G C; Ando, S I; Brooks, S C; Pollard, M J; Picton, P (American journal of physiology. Regulatory, integrative and comparative physiology, 2001)
Lower body negative pressure (LBNP; -5 and -15 mmHg) was applied to 14 men (mean age 44 yr) to test the hypothesis that reductions in preload without effect on stroke volume or blood pressure increase selectively muscle sympathetic nerve activity (MSNA), but not the ratio of low- to high-frequency harmonic component of spectral power (P(L)/P(H)), a coarse-graining power spectral estimate of sympathetic heart rate (HR) modulation. LBNP at -5 mmHg lowered central venous pressure and had no effect on stroke volume (Doppler) or systolic blood pressure but reduced vagal HR modulation. This latter finding, a manifestation of arterial baroreceptor unloading, refutes the concept that low levels of LBNP interrogate, selectively, cardiopulmonary reflexes. MSNA increased, whereas P(L)/P(H) and HR were unchanged. This discordance is consistent with selectivity of efferent sympathetic responses to nonhypotensive LBNP and with unloading of tonically active sympathoexcitatory atrial reflexes in some subjects. Hypotensive LBNP (-15 mmHg) increased MSNA and P(L)/P(H), but there was no correlation between these changes within subjects. Therefore, HR variability has limited utility as an estimate of the magnitude of orthostatic changes in sympathetic discharge to muscle.